Job Growth and Finance : Are Some Financial Institutions Better Suited to Early Stages of Development Than Others? - Cull, Robert; Xu, L. Colin (2012)
This paper combines firm-level data from 89 countries with updated country-level data on financial structure, and uses two estimation approaches. It finds that in low-income countries, labor growth is swifter in countries with a higher level of private credit/gross domestic product; the positive effect of bank credit is especially pronounced in industries that depend heavily on external finance; and banking development is positively associated with more physical and human capital investment. These findings are consistent with predictions from new structural economics. In high-income countries, labor growth rates are increasing in the level of stock market capitalization, which is also consistent with predictions from new structural economics, although the analysis is unable to provide evidence that the association is causal. It finds no evidence that small-scale firms in low-income countries benefit most from private credit market development. Rather, the labor growth rates of larger, capital-intensive firms increase more with the level of private credit market development, a finding consistent with the history-based political economy view that banking systems in low-income countries serve the interests of the elite, rather than providing broad-based access to financial services.